2007
DOI: 10.1007/s10661-007-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heavy metal levels in water, sediment and tissues of tench (Tinca tinca L., 1758) from Beyşehir Lake (Turkey)

Abstract: In the present study, some heavy metals (Cu, Fe, Zn and Mn) were seasonally determined in water, sediment and some tissues of fish Tinca tinca from Beyşehir Lake, which is an important bird nesting and visiting area, a water source for irrigation and drinking. In the water, Fe has the highest concentrations among the studied metals. Generally, the metal concentrations increased in the hottest period decreased in warm seasons. Results for levels in water were compared with national and international water quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 20 publications
6
16
0
Order By: Relevance
“…Zn concentration ranged from 8.20 to 23.75 mg kg -1 in this study. These values match with results of Tekin-Özan and Kir (2006) and Tekin-Özan (2008) who have determined Zn content for S. lucioperca, C. carpio and L. cephalus in Beyşehir Lake. Zn concentrations in all fish specimens of this study were lower than all guidelines limits in Table 4, but were inacceptable level with regard to diet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Zn concentration ranged from 8.20 to 23.75 mg kg -1 in this study. These values match with results of Tekin-Özan and Kir (2006) and Tekin-Özan (2008) who have determined Zn content for S. lucioperca, C. carpio and L. cephalus in Beyşehir Lake. Zn concentrations in all fish specimens of this study were lower than all guidelines limits in Table 4, but were inacceptable level with regard to diet.…”
Section: Discussionsupporting
confidence: 91%
“…Heavy metal content of Cyprinus carpio, Leuciscus cephalus and Stizostedion lucioperca were studied by Tekin-Özan andKir (2006 and2008). Tekin-Özan (2008) and Aktumsek and Gezgin (2011) reported heavy metal content in water, sediment and tissues of Tinca tinca.…”
Section: Beyşehir Gölü'ndeki Dokuz Balık Türünün Kas Dokularındaki Bamentioning
confidence: 99%
“…This observation was similar to the observation of other workers for many species of fish in different aquatic systems (Tekin-Ozan 2008;Yilmaz and Dogan 2008). This can be attributed to the fact that Zn is present in many enzymes (Karadede and Unlu 2000;Alhas et al 2009).…”
Section: Distribution Of Metals In Fish and Shrimpsupporting
confidence: 92%
“…Among the analyzed metals, the highest and lowest metals were Fe and Cd. Similar results were reported in Beyler Reservoir (Fındık, 2013), Hazar Lake (Karadede-Akın, 2009), Karataş Lake (Başyiğit and Tekin-Özan, 2013), Kızılırmak River (Akbulut and Akbulut, 2010), Beyşehir Lake (Tekin-Özan, 2008). Ghaffar et al (2008), reported that Fe facilities the precipitation of other metals and found at low levels when precipitation occurs.…”
Section: Resultssupporting
confidence: 70%
“…Cd, Cu and Mo levels varied significantly (p<0.05) from season to season. Tekin-Özan (2008) reported that the Cu and Zn levels were highest in spring, while Fe and Mn were in autumn in Beyşehir Lake's sediment. In Beyler reservoir sediment, Fe, Al, Zn, Cu, Mn and B were highest in summer, while Cr, Ni, Cd and Pb were in spring (Fındık and Turan, 2012).…”
mentioning
confidence: 99%